The level of concern for oral health in children visiting the Dental Hospital of Hasanuddin University - Sherly Horax; Eri Hendra Jubhari; Aldy Anzhari Ayub (Makassar Dental Journal PDGI Makassar, 2020)
Background: The visit of children to the dentist to have their teeth checked is not routinely done. There is still a lack of awareness or concern for children about dental health due to a lack of knowledge about preventive and dental care in children to get opti-mal oral health. Aim: To determine the relationship between the level of motivation, cooperation and knowledge about oral dental health on oral health. Methods: Analytical observational research and cross sectional study approach was carried out in September 2016 at the Dental Clinic for Children, Dental Hospital of Hasanuddin University. With the accidental sampling technique, all children aged 6-17 years who visited the clinic filled out a questionnaire and performed an oral status check. Results: The Kruskall wallis test showed that there was a significant relationship between the level of motivation and knowledge of children on oral health and the level of visits and high levels of cooperation was dominated by patients who were picked up by the operator. Conclusion: There is a relationship between the level of motivation and knowledge about children's oral health and the highest level of cooperation is dominated by patients who are picked up by the operator.